Potential Effect of Nonsteroidal Anti-Inflammatory Drugs on Certain Hormones in Females in Basrah City - Zahraa Attaala Almiah; Hadeel S. Al Ali; Manal N. Al-Hayder; Azza Sajid Jabbar; Qasim Hussein (College of Pharmacy University of Baghdad, 2024)
Nonsteriodial anti-inflammatory drugs (NSAIDs) are commonly used by women to control pain associated with menstruation period. The main objective of this study is to determine whether use of NSAIDs has impact on the levels of certain hormones in females or not. A cross-sectional study was conducted between participant women who were taken one of the following NSAIDs including diclofenac, ibuprofein and mefenamic acid, for at least one year and more during menstruation and control women (did not take any medication). Levels of follicle stimulating hormone (FSH), Luteinizing hormone (LH), testosterone, prolactin and thyroid stimulating hormone (TSH) were measured by i-CHROMA method. The results showed that the level of LH significantly increased in groups of women who were taken NSAIDs during menstruation period, as well as diclofenac and mefenamic acid have a significant effect on the level of prolactin However, no clear changes were observed in the levels of FSH and testosterone at any type of NSAIDs that were used by the participant women in this study, the results were variable. No clear associations were observed between types of analgesic use and FSH, testosterone, prolactin and TSH. Further studies are required to confirm definite effect of NSAIDs on these hormones.